Student attitudes on education for employee self-marketing - Zvjezdana Penava Brekalo (Ekonomski Vjesnik, 2013)
This paper examines the attitudes of students on employee self-marketing, i.e. on education for employee self-marketing at the university as well as on acquiring adequate knowledge and skills in the process of applying for jobs on the labour market in Croatia. This study explores the attitudes of third-year undergraduate students and second-year graduate students at the Faculty of Economics and Tourism “Dr. Mijo Mirkovic” in Pula and the Faculty of Economics in Osijek. The study provides an insight into students’ opinions about lectures and workshops on employee self-marketing aimed at preparing students for a more efficient transition from university to the labour market.